Relapsing-Remitting Multiple Sclerosis Effectively Treated with Peginterferon Beta-1 - Vinall, Phil (MD Conference Express, 2014)
Significantly more subjects with relapsing-remitting multiple sclerosis achieved freedom from measured disease activity when treated with peginterferon beta-1a every 2 weeks compared with those who were treated with peginterferon beta-1a every 4 weeks or placebo. This article presents results from a post hoc analysis of 48-week data from the Efficacy and Safety Study of BIIB017 (PEGylated Interferon Beta-1a) in Participants With Relapsing Multiple Sclerosis trial [ADVANCE; NCT00906399].